SIMULASI NUMERIK TAHANAN KAPAL GILLNET MENGGUNAKAN PENDEKATAN COMPUTATIONAL FLUIDS DYNAMICS - Hutauruk, Ronald Mangasi (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
A good designer of fishing vessels must be able to estimate ship resistances which treat-ment on ship during fishing operations. Such resistances information will be used as themilestones in the main and the auxiliary engine matching in which the chosen engine must besuitable to the needs of thrust at the certain velocity. The magnitude of ship resistance can bedetermined by some methods e.g. towing tank methods, using ship resistance graph of seriesship models on various velocities, using approaching formula from statistic (with regression)and the last by using Computational Fluid Dynamics (CFD). CFD is the most economic inship resistance study with result almost approaching the manual test. The ship was gillnetter 5in gross tonnage. Its model was investigated by using numerical simulation of CFD. The dataof resistance are processed with ANSYS CFX version 14. The result shows the vesselresistance was 6,43 kN and engine power was 29,76 kW at maximum speed (9 knots). Itimplys the similiar conclusion by using manual test and approaching formula.